The impact of hospital-specific guidelines on carbapenem use and patient outcomes in a setting for high endemicity with multidrug-resistant gram-negative bacilli - Cemre Boşnak; Şeyda Betül Fındık; Muhammed Atay; Ward Fakhouri; Sada Babazade; Eda Karadoğan; Gökhan Metan; Ömrüm Uzun (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract